Context effects on repair of 5′‐overhang DNA double‐strand breaks induced by Cas12a in Arabidopsis - Sébastien Lageix; Miguel Hernandez; Maria E. Gallego; Jérémy Verbeke; Yannick Bidet; Sandrine Viala; Charles I. White (Plant Direct)
Abstract Sequence‐specific endonucleases have been key to the study of the mechanisms and control of DNA double‐strand break (DSB) repair and recombination, and the availability of CRISPR‐Cas nucleases over the last decade has driven rapid progress in the understanding and application of targeted recombination in many organisms, including plants. We present here an analysis of recombination at targeted chromosomal 5′ overhang DSB generated by the FnCas12a endonuclease in the plant, Arabidopsis thaliana. The much‐studied Cas9 nuclease cleaves DNA to generate blunt‐ended DSBs, but relatively less is known about the repair of other types of breaks, such as those with 5′‐overhanging ends. Sequencing the repaired breaks clearly shows that the majority of repaired DSB carry small deletions and are thus repaired locally by end‐joining recombination, confirmed by Nanopore sequencing of larger amplicons. Paired DSBs generate deletions at one or both cut‐sites, as well as deletions and reinsertions of the deleted segment between the two cuts, visible as inversions. While differences are seen in the details, overall the deletion patterns are similar between repair at single‐cut and double‐cut events, notwithstanding the fact that only the former involve cohesive DNA overhangs. A strikingly different repair pattern is however observed at breaks flanked by direct repeats. This change in sequence context results in the presence of a major alternative class of repair events, corresponding to highly efficient repair by single‐strand annealing recombination.